Simulation of Routing Option by Using Two Layers Fuzzy Logic and Dijkstra’s Algorithm in MATLAB 7.0 - Joni Ganda (President University, 2016)
This project is aimed to create simulation software which can give an optimal route based on the condition given by the user. Travelling salesman problem, fuzzy logic and Dijkstra’s algorithm will be used as benchmark of the software. The program will be developed in MATLAB 7.0. Fuzzy logic will process the current condition of the map become input for Dijkstra’s algorithm. The result of the program will be an optimal route from three points of view; distance, density, and confusion. In order to verify the result of the program, it will be compared with the result of people’s opinions in the same problem.Keywords: Routing, fuzzy logic, Dikstra’s algorithm, Matlab